Hubungan Motivasi Kerja Dengan Perilaku Caring Perawat Di Ruang HCU Anak RSUD Dr. Saiful Anwar Malang - Deti Noffita; Reny Tri Febriani; Nining Loura S (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
ABSTRACT Nurses' caring behavior plays a role in improving the quality of service in hospitals. Caring behavior in the intensive care unit could be influenced by nurses' work motivation. This study aims to determine the relationship between work motivation and caring behavior of nurses in the Children's HCU. This research was a quantitative research study with a correlative analytical type. A sample of nurses in the Children's HCU and PICU at RSUD Dr. Saiful Anwar Malang, numbering 55 people. The research instrument used was a questionnaire. The research results showed that the majority of respondents had strong work motivation (60,0%). Most respondents had good caring behavior (56,4%). The Pearson Correlation statistical test produces a p-value = 0,000. The results of statistical tests show that there was a relationship between work motivation and the caring behavior of nurses in the Children's HCU Room at RSUD Dr. Saiful Anwar Malang. Nurses who have strong motivation tend to provide good service, but if nurses have weak work motivation, this makes the nurse lazy in carrying out activities, namely serving and caring for patients, in this case, behaving caringly towards patients. Keywords: Work motivation, caring behavior, nurses